Glass tube-coated TiO2 nanostructure for degradation of methylene blue: an experimental and design of column photocatalytic reactor - Rahmat Hidayat; Ganjar Fadillah; Shin-Ichi Ohira (Universitas Islam Indonesia, 2023)
This work presents the successfully of TiO2 nanostructure synthesis using manual grinding combined hydrothermal method for photocatalyst. XRD confirmed that TiO2 was arranged by anatase and rutile phase with crystal size of 18.54 nm. Characterization of digital microscope shows the spread of catalyst on the glass tube surface, which can be observed furthermore using interactive 3D surface plot. Band gap energy determination from UV-Vis spectroscopy scanning shows the minimum energy that is required to facilitate electron-hole generated. In 20 min of irradiation, TiO2 existence can completely decompose MB (100%) that can be presented by TiO2 absence. Degradation of MB is higher effective in acidic condition which optimum pH of 5. Using first order reaction, glass tube-coated TiO2 has rate constant of 0.2102 min-1, 1.5 times faster than bare glass tube. This enhancement proves that the designed reactor has good prospect for organic pollutant treatment. Moreover, compared with other reported study, this system provides relatively more effective of MB photodegradation.